Ethyl 4-[(2-hydroxyethyl)amino]-2-(4-methoxyphenyl)-1-methyl-5-oxo-2,5-dihydro-1H-pyrrole-3-carboxylate - Fatin Nur Ain Abdul Rashid; Mohd Fazli Mohammat; Mohd Abdul Fatah Abdul Manan; Ayisy Amirul Afti Bakhtiar Afendy; David B. Cordes; Aidan P. McKay (IUCrData)
In the title compound, C17H22N2O5 the pyrrolidine ring is almost planar and subtends a dihedral angle of 85.77 (7)° with the pendant phenyl ring. An intramolecular N—H...O hydrogen bond generates an S(6) loop. In the crystal, the compound forms inversion dimers through O—H...O hydrogen bonds from the disordered hydroxyl group to either the hydroxyl or ester carbonyl O atom of the adjacent molecule.